"That's Why I Do What I Do": Southern Black feminism in philosophy. Issue 12 (28th October 2021) - Stewart, Lindsey
Abstract: Alice Walker claims that the "advantageous heritage" of Black southern life is replete with intellectual meat for thinking and writing. How might the insights found in this "advantageous heritage" enrich our discussions of Black feminism in philosophy? Taking stock of this "advantageous heritage" is no mean feat in the discipline of philosophy as it sits at the intersection of two subfields that are already marginalized: Black feminist philosophy and southern philosophy. To help situate southern Black feminist philosophy, I draw upon Kristie Dotson's model of "inheritance maps, " or an "attempt to take stock of what one has been given in a particular project and what one inherits as work yet to do." Focusing primarily on the theme of refusal, I develop an "inheritance map" that lays out aspects of southern Black feminism that I have inherited from Angela Davis's Blues Legacies and Black Feminism .